2019
DOI: 10.1002/jia2.25262
|View full text |Cite
|
Sign up to set email alerts
|

Does free schooling affect pathways from adverse childhood experiences via mental health distress to HIV risk among adolescent girls in South Africa: a longitudinal moderated pathway model

Abstract: Introduction Adolescent girls are at high risk of HIV infection in sub‐Saharan Africa. Mental health distress, driven by adverse childhood experiences (ACEs) such as abuse, poverty and family HIV, may be an important driver of HIV risk behaviour among adolescent girls, while education may mitigate these risks. This study aimed to develop an empirically based theoretical model between ACEs, mental health distress and HIV risk behaviour among adolescent girls in South Africa and to investigate the potential mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Researchers referred to these categories as "adverse psychological experiences" (Danese et al, 2009, p. 3). Furthermore, studies in four countries on three different continents, Iraq, South Africa, the Philippines, and Brazil concurred that poverty significantly contributed to ACEs (Al-Shawi & Lafta, 2015;Meinck, Orkin, & Cluver, 2019;Ramiro et al, 2010;Soares et al, 2016Soares et al, ) 2016. In an Iraqi study, poverty, education, personality type, and presence in a war zone were associated with high ACEs (Al-Shawi & Lafta, 2015).…”
Section: Developing Aces From a Global Perspectivementioning
confidence: 92%
“…Researchers referred to these categories as "adverse psychological experiences" (Danese et al, 2009, p. 3). Furthermore, studies in four countries on three different continents, Iraq, South Africa, the Philippines, and Brazil concurred that poverty significantly contributed to ACEs (Al-Shawi & Lafta, 2015;Meinck, Orkin, & Cluver, 2019;Ramiro et al, 2010;Soares et al, 2016Soares et al, ) 2016. In an Iraqi study, poverty, education, personality type, and presence in a war zone were associated with high ACEs (Al-Shawi & Lafta, 2015).…”
Section: Developing Aces From a Global Perspectivementioning
confidence: 92%
“…A South African study of HIV risk, adverse childhood experiences (ACEs), adolescent mental health, and free schooling for adolescent girls, found that relationships between ACEs and HIV risk behaviour were mediated by internalizing and externalizing symptoms [62]. Free schooling was associated with fewer externalizing symptoms, suggesting that the mental health-promoting effects of free education confer some protection against HIV risk.…”
Section: The Relationship Of Mental Health To Hiv Prevention Behavioursmentioning
confidence: 99%
“…Cash transfers led to better HIV risk outcomes for boys and girls, but better mental health outcomes for boys [57]. Nevertheless, for vulnerable girls, access to social resources such as free school or cash transfers reduced behaviours directly and indirectly related HIV risk [57,62]. HIV programme implementers must also consider how the social vulnerabilities of adolescents may increase the risk of coercive participation in HIV prevention or may indirectly create barriers to interventions (e.g.…”
Section: The Relationship Between Mental Health and Hiv Prevention Behavioursmentioning
confidence: 99%
“…It has the added benefit of simplifying data presentation when examining multiple model specifications, and has been used to capture HIV risk in prior studies [e.g. 30,31]. We created composite behavioral risk scores using four binary indicators: no condom use at last sex; early sexual debut (<16 years); three or more lifetime sexual partners; and age-disparate partnerships (>5 years difference).…”
Section: Methodsmentioning
confidence: 99%